2014
DOI: 10.1089/jpm.2013.0593
|View full text |Cite
|
Sign up to set email alerts
|

Response to Pain Management among Patients with Active Cancer, No Evidence of Disease, or Chronic Nonmalignant Pain in an Outpatient Palliative Care Clinic

Abstract: Although median pain scores improved at follow-up, less than half of patients were responders. Patients with AC had a significantly better response rate than NED patients and a lower pain score than NLLI patients at follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…14e16 Such pain may predate their cancer (e.g., preexisting knee osteoarthritis), may be exacerbated by cancer treatments and procedures (e.g., preexisting low back pain exacerbated by being sedentary after cancer-related surgery), may be caused by ongoing active disease (e.g., chest pain in a patient with lung cancer), or may be caused by sequelae of the cancer or its treatment (e.g., lymphedema-related pain in a patient with surgically treated breast cancer, lifelong neuropathy in a patient previously treated with paclitaxel). 17 The American Society of Clinical Oncology recently released a guideline on the management of chronic pain in cancer survivors 18 that has significant overlap with the Centers for Disease Control and Prevention (CDC) Guideline for prescribing opioids for chronic pain . 1 Both emphasize a careful weighing of the risks and benefits of long-term opioid therapy (LTOT), recommend the use of monitoring strategies such as urine drug testing and practitioner database monitoring programs, and encourage providers to address opioid misuse behaviors and treat addiction when it occurs.…”
Section: Introductionmentioning
confidence: 99%
“…14e16 Such pain may predate their cancer (e.g., preexisting knee osteoarthritis), may be exacerbated by cancer treatments and procedures (e.g., preexisting low back pain exacerbated by being sedentary after cancer-related surgery), may be caused by ongoing active disease (e.g., chest pain in a patient with lung cancer), or may be caused by sequelae of the cancer or its treatment (e.g., lymphedema-related pain in a patient with surgically treated breast cancer, lifelong neuropathy in a patient previously treated with paclitaxel). 17 The American Society of Clinical Oncology recently released a guideline on the management of chronic pain in cancer survivors 18 that has significant overlap with the Centers for Disease Control and Prevention (CDC) Guideline for prescribing opioids for chronic pain . 1 Both emphasize a careful weighing of the risks and benefits of long-term opioid therapy (LTOT), recommend the use of monitoring strategies such as urine drug testing and practitioner database monitoring programs, and encourage providers to address opioid misuse behaviors and treat addiction when it occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Full text review of 7 articles identified 5 eligible articles, published between 2014 and 2020, that were included in this review (Figure 1). Of the 5 included studies, 4 were performed in the United States (Childers et al 2015;Hui et al 2020;Jennings et al 2014;Molony et al 2014) and 1 in Hong Kong (Chan et al 2018). All included studies were observational: 2 were cohort (Chan et al 2018;Jennings et al 2014) and 3 were cross-sectional studies (Childers et al 2015;Hui et al 2020;Molony et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 5 included studies, 4 were performed in the United States (Childers et al 2015;Hui et al 2020;Jennings et al 2014;Molony et al 2014) and 1 in Hong Kong (Chan et al 2018). All included studies were observational: 2 were cohort (Chan et al 2018;Jennings et al 2014) and 3 were cross-sectional studies (Childers et al 2015;Hui et al 2020;Molony et al 2014). Two studies measured outcomes over time (initial visit and first followup) (Chan et al 2018;Jennings et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic pain, defined as persistent pain lasting longer than three months (13), is common among cancer survivors and may greatly impair their well-being and quality of life (QOL) (14)(15)(16). This type of pain may precede cancer diagnosis, may be caused by ongoing active disease, may be induced by anticancer treatments and procedures, or may be caused by cancer sequelae or its treatment (17,18).…”
Section: Introductionmentioning
confidence: 99%